From Interaction to Intention: Investigating Key Drivers of User Retention in Digital Marketplaces - Nugraheni, Dinar Mutiara; Noranita, Beta; Isy, Auliya Daffa (Scientific Journal of Informatics, 2025)
Purpose: The rapid evolution of digital marketplaces has heightened the importance of understanding the drivers of user engagement. While prior research has focused on perceived ease of use and perceived usefulness, limited attention has been given to the impact of emerging interactive features such as affordances (metavoicing, guidance shopping, visibility, and trading). This study aims to bridge that gap by examining the combined effects of metavoicing, guidance shopping, visibility, trading, perceived ease of use, and perceived usefulness on users' perceptions and their continued intention to use a digital marketplace platform. These factors interact synergistically to create a cohesive and engaging user experience. Methods: A quantitative research design was adopted, utilizing structured questionnaires distributed to 200 active users of a leading Indonesian marketplace platform. Structural Equation Modeling (SEM) was employed to test the hypothesized relationships among the study variables. Result: The results reveal that affordances (metavoicing, guidance shopping, visibility, and trading) significantly influence user behavioral intention through their impact on perceived usefulness and ease of use, with trading affordance showing the strongest effect (β = 0.469) and perceived usefulness being the primary driver of behavioral intention (β = 0.753). Novelty: This study provides valuable insights for Digital marketplace developers to enhance user engagement by a comprehensive Digital Marketplace Requirements Framework that structures implementation around four core affordance categories: Trading Requirements (payment systems, checkout processes), Visibility Requirements (product display, visual search), Metavoicing Requirements (communication systems, review mechanisms), and Guidance Shopping Requirements (personalization, search functionality).